Research Profile of Inquiry on Physics Learning During the COVID-19 Pandemic - Binar Kurnia Prahani; Budi Jatmiko; Tan Amelia; Kirana Aureola Arzak; Nova Allysa Qotrunnada; Shalsa Billa Ardhana Neswary (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the application of inquest model learning during the COVID-19 pandemic. This research method reviewed literature and research articles as many as 15 articles that met the criteria both nationally and internationally which included inquiry models and physics learning when the pandemic was used in this research. Data collection is done indirectly and in the form of secondary data. The results showed that 1) The application of the inquiry learning model during the COVID-19 pandemic in improving students' understanding and critical and creative thinking skills increased significantly. 2) The use of online learning tools based on inquiry learning models shows an increase in students' understanding of concepts and critical thinking skills. 3) Online learning tools are categorized as feasible for use in physics learning during the COVID-19 pandemic. 4) It takes a long time to implement the inquiry learning model as long as online learning media, especially e-modules, have not met the demands of 21st century learning